Percutaneous transhepatic intervention for malignant biliary obstruction - Binh, Le Trong; Khoi, Tran Van; Dung, Hoang Anh; Hanh, Huyen Ton Nu Hong; Pon, Le Nguyen; Tuan, Le Minh; Hung, Dang Quang (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Biliary obstruction is a serious clinical condition resulting from either benign or malignant etiologies. For malignant obstruction, curative resection is rarely performed due to disease progression, thus decompression drainage is the management of choice. Percutaneous transhepatic drainage and stenting are effective alternative treatments to surgical bypass and endoscopic biliary drainage when these two modalities are contraindicated. Percutaneous biliary intervention is safe and effective in both drainage and restoration of bile flow with high successful rate and acceptable risk of complication. Multidisciplinary approach, proper patient selection, careful image review and comprehensive knowledge of available techniques, success rates and complications are utmost importance for a successful procedure.